Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1074/mcp.ra120.002295
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific N-glycosylation Characterization of Recombinant SARS-CoV-2 Spike Proteins

Abstract: The glycoprotein spike (S) on the surface of SARS-CoV-2 is a determinant for viral invasion and host immune response. Herein, we characterized the site-specific N-glycosylation of S protein at the level of intact glycopeptides. All 22 potential N-glycosites were identified in the S-protein protomer and were found to be preserved among the 753 SARS-CoV-2 genome sequences. The glycosites exhibited glycoform heterogeneity as expected for a human cell-expressed protein subunit. We identified masses that correspond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(129 citation statements)
references
References 48 publications
2
119
0
Order By: Relevance
“…When the site-specific N-linked glycans are mapped onto the prefusion structure of the SARS-CoV-2 S ectodomain ( 63 ), the resulting model exhibited substantially higher levels of glycan-free surface than that revealed by structures of fully glycosylated, trimeric HIV-1 Env ectodomains ( 65 , 66 ). This suggests that the SARS-CoV-2 S protein is covered by a less dense and less effective glycan shield compared to viral glycoproteins from HIV-1 ( 36 , 66 ) and Lassa virus ( 67 ), which may be beneficial for the induction of humoral immunity and could be good news for a SARS-CoV-2 vaccine ( 68 ).…”
Section: Glycan Shield Of the Sars-cov-2 S Glycoproteinmentioning
confidence: 99%
“…When the site-specific N-linked glycans are mapped onto the prefusion structure of the SARS-CoV-2 S ectodomain ( 63 ), the resulting model exhibited substantially higher levels of glycan-free surface than that revealed by structures of fully glycosylated, trimeric HIV-1 Env ectodomains ( 65 , 66 ). This suggests that the SARS-CoV-2 S protein is covered by a less dense and less effective glycan shield compared to viral glycoproteins from HIV-1 ( 36 , 66 ) and Lassa virus ( 67 ), which may be beneficial for the induction of humoral immunity and could be good news for a SARS-CoV-2 vaccine ( 68 ).…”
Section: Glycan Shield Of the Sars-cov-2 S Glycoproteinmentioning
confidence: 99%
“…The studies also detected one O-glycopeptide occupied at sites, distinct from the predicted furin cleavage site at the S1/S2 boundary. 6 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…The exact structures of at least 22 N-linked glycans were successfully established by mass spectrometry [17] and independently confirmed. [18] In addition, the nucleocapsid protein is decorated with O-glycans and N-glycans, at 7 and 2 confirmed sites, respectively. [19] The glycans of the spike protein act as a shield to thwart the host immune response, but a recent study has shown that N-glycans at two sites (N165 & N234) modulate the conformational dynamics of the receptor-binding domain (RBD).…”
Section: The Sars-cov-2 Machinery Landscapementioning
confidence: 99%